THE AUTHENTICITY OF MUTTAFAQ HADITHS BY IBN KHUZAIMAH AND AL-HĀKIM: A REVIEW - Amaliyah, Nailah; Redha, Inaya Hartina; Hermanto, Muhammad Fadli; Putra, Ferangga Wimbodyo Sunarto; Muhid, Muhid (LP2M Ma'had Aly Hasyim Asy'ari Pesantren Tebuireng, 2023)
The muttafaq hadith, apart from Ṣaḥīḥ Bukhari-Muslim, is not widely known, even though there are other Sahih books besides those two. Among the Sahih books are Ṣaḥīḥ Ibn Khuzaimah and Mustadrak al-Hakim. While the authenticity of the muttafaq 'alaih (The hadith of Bukhari-Muslim) is clear and accepted by all Muslims, the same cannot be said for the authenticity of muttafaq hadith outside of Bukhari-Muslim. There is an assumption that the similarity in the chain of narration (sanad) of muttafaq hadith narrated by Imams apart from Bukhari-Muslim does not always indicate the authenticity of the hadith. To test this assumption, this research uses four samples of muttafaq hadith on the topic of